Senior hejter – fakt czy mit? W świetle badań nad senioralną komunikacją online - Głódź, Natalia (Kultura-Społeczeństwo-Edukacja, 2023)
The Internet is a socially valued asset. Unfortunately, the dynamic development of digital space, as well as the spread of online communication among seniors, have contributed to the emergence of a new phenomenon, hitherto unknown in this age group, the so-called hate speech. This article presents a theoretical and research perspective on an aspect of online communication in cyberspace. The aim of the research undertaken was to observe and investigate the problem of hate speech and aggression among senior Internet users. The research was conducted using a quantitative method on a group of 61 seniors who actively use the Internet. In addition, it was supplemented with insights from a four-month observation of Facebook groups dedicated to 60 plus users. The results obtained from the research indicate that the phenomenon of hate speech is a real one in the senior group of Internet users. Consequently, this raises the need for educational and preventive measures.